2023
DOI: 10.1002/adma.202304896
|View full text |Cite
|
Sign up to set email alerts
|

A Bioinspired Injectable, Adhesive, and Self‐Healing Hydrogel with Dual Hybrid Network for Neural Regeneration after Spinal Cord Injury

Abstract: Hydrogel‐based regenerated scaffold shows promise as a platform for neural regeneration following spinal cord injury (SCI). Nevertheless, the persistent problem of poor mechanical strength and limited integration with the host tissue still exists. In this study, we developed a bioinspired hydrogel with highly sophisticated features for neural regeneration after SCI. The hydrogel is composed of DOPA‐grafted chitosan and a designer peptide, offering a unique set of qualities such as being injectable, having self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Biomaterials that can manipulate the phenotypes of immune cells have proved effective in improving treatment outcome of SCI. 44 Since CUR could regulate the polarization of microglia, 28 the anti- inflammatory effect of PFCN was investigated by analyzing the M1/M2 polarization of microglia. BV2 cells were pretreated with lipopolysaccharide (LPS) to establish an inflammation model in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomaterials that can manipulate the phenotypes of immune cells have proved effective in improving treatment outcome of SCI. 44 Since CUR could regulate the polarization of microglia, 28 the anti- inflammatory effect of PFCN was investigated by analyzing the M1/M2 polarization of microglia. BV2 cells were pretreated with lipopolysaccharide (LPS) to establish an inflammation model in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that activated microglia after SCI could polarize to two distinct subsets, i.e., cytotoxic pro-inflammatory (M1) phenotype and pro-repair anti-inflammatory (M2) phenotype. 44 The M1 microglia plays an important role in the mediation of inflammation after SCI, whereas M2 microglia represents immunosuppression, upregulation of extracellular matrix components, and tissue repair. Biomaterials that can manipulate the phenotypes of immune cells have proved effective in improving treatment outcome of SCI.…”
Section: Resultsmentioning
confidence: 99%
“…CHT is a polycationic copolymer formed by the N -deacetylation of chitin and comprises glucosamine and N -acetylglucosamine units . It is widely exploited on account of its cytocompatibility, antibacterial and hemostatic activities, biodegradability, and muco-adhesiveness. ,, Furthermore, CHT dissolves in an acidic solution (such as acetic acid) and is insoluble under neutral and alkaline conditions. CHT is soluble at a pH lower than ∼6.3 and in ferric solutions through coordination interaction among ferric ions, hydroxyl groups, and amino groups .…”
Section: Properties Of Polysaccharides Used In Dn Hydrogelmentioning
confidence: 99%
“…138 It is widely exploited on account of its cytocompatibility, antibacterial and hemostatic activities, biodegradability, and muco-adhesiveness. 80,138,139 Furthermore, CHT dissolves in an acidic solution (such as acetic acid) and is insoluble under neutral and alkaline conditions.…”
Section: Cellulosementioning
confidence: 99%
“…However, to ensure their neuroregenerative function, further in vivo transplantation experiments are necessary. Furthermore, based on hydrogel-based bioinks, the regenerative scaffolds exhibit a wide range of prospects as a novel platform for treating nervous system-related diseases such as spinal cord injury, drug delivery, neural regeneration, and repair . For the fabricated constructs used in transplantation, the ultimate goal is to reconstruct the cellular microenvironment that can process various signals and cues, providing guidance for cell behavior and function.…”
Section: Bioinks For 3d Bioprinting Of Tissues and Organsmentioning
confidence: 99%